The impact of German job protection, legislation on job, creation in small establishments: An application of the regression discontinuity design - Derik Burgert (Universität Lüneburg, Forschungsinstitut Freie Berufe (FFB), 2005)
One proposal frequently raised to increase flexibility of the German labour market is the liberalization of the job protection law. It applies to those establishments with more than a cut-off number of employees. The argument examined in this paper is that this step in legal regulation hinders small enterprises from job creation. Changes in the cut-off number in the late 1990's provide the basis for estimating this effect. The evaluation approach is a Regression Discontinuity Design using these changes as natural experiments. Local treatment effects can be estimated non-parametrically by local linear regression. The data base used is the IAB establishment panel. The paper is the first one to exploit the policy changes named above and controlling for self-selection into the treatment job protection using minimal assumptions concerning model specification. The results are in line with earlier studies finding no evidence for hindering effects on job growth in small establishments. – – Eines der am häufigsten genannten Vorschläge, um den deutschen Arbeitsmarkt zu flexibilisieren, ist die Lockerung des Kündigungsschutzgesetzes. Es findet Anwendung für Betriebe, die einen Schwellenwert an Mitarbeitern überschreiten. Die These, die in dieser Arbeit untersucht werden soll, ist die, dass diese Schwelle im Gesetz Kleinbetriebe daran hindere, Einstellungen vorzunehmen.Änderungen im Schwellenwert in den späten 1990er Jahren bilden die Basis für die Schätzung dieses Effektes. Der Auswertungsansatz ist ein Regression Discontinuity Design, für das diese Änderungen als natürliche Experimente verwendet werden. Lokale Treatmenteffekte können nicht-parametrisch mittels lokaler linearer Regression geschätzt werden.Dieses Papier ist das erste, das die oben genannten Gesetzesänderungen benutzt, um für Selbstselektion zu kontrollieren, und sich dabei auf minimale Annahmen bezüglich der Modellspezifikation stützt. Die Ergebnisse stimmen mit früheren Untersuchungen überein, die keine solchen beschäftigungshemmenden Effekte für Kleinbetriebe nachweisen konnten.
Keywords: J23; K31; M51; 330; employment protection; threshold effects; RDD; local linear regression; Germany; Kündigungsschutz; Schwellenwerte-Effektes; RDD; lokale lineare Regression; Deutschland; Kündigungsschutz; Beschäftigungseffekt; KMU; Schätzung; Deutschland